1993
DOI: 10.1590/s0034-89101993000400007
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reported weight: a study of urban brazilian adults

Abstract: SCHMIDT, M.I. et al. Validity of self-reported weight -A study of urban brazilian adults. Rev. Saúde Pública, 27: 271-6, 1993. In order to evaluate the validity of self-reported weight for use in obesity prevalence surveys, self-reported weight was compared to measured weight for 659 adults living in the Porto Alegre county, RS Brazil in 1986-87, both weights being obtained by a technician in the individual's home on the same visit. The mean difference between self-reported and measured weight was small (-0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
2
35

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 8 publications
8
60
2
35
Order By: Relevance
“…Despite the small magnitude, the means of the difference between self-reported and measured weight in our population were greater than that observed by Schmidt et al 16 in a sample of the general population of Porto Alegre, in Southern Brazil, between 15 and 64 years old (mean=-0.06 kg; sd=3.16 kg). Another difference between these studies was that, in Porto Alegre, women tended to underestimate their weight and men to overestimate it, according to a pattern identified by others 15 .…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Despite the small magnitude, the means of the difference between self-reported and measured weight in our population were greater than that observed by Schmidt et al 16 in a sample of the general population of Porto Alegre, in Southern Brazil, between 15 and 64 years old (mean=-0.06 kg; sd=3.16 kg). Another difference between these studies was that, in Porto Alegre, women tended to underestimate their weight and men to overestimate it, according to a pattern identified by others 15 .…”
Section: Discussioncontrasting
confidence: 89%
“…In this case, self-information is used. Comparing self-information with direct measurement is essential and several studies have shown its validity in Brazil and in other countries 5,15,16,20 .…”
Section: Introductionmentioning
confidence: 99%
“…weight, which is subject to recall bias. However, on the basis of our previous findings concerning weight recall for Brazilian women studied outside of pregnancy (Schmidt et al, 1993), we believe that this measurement bias is probably small. In conclusion, in a population generally representative of women attending Brazilian public health clinics in major cities, the prevalence of pre-obesity and obesity prior to pregnancy was high, and approximately two-thirds of the women did not achieve the weight gain recommended by the Institute of Medicine.…”
Section: Discussionmentioning
confidence: 86%
“…An additional limitation is that prepregnancy weight was reported and not objectively measured, and thus subject to recall bias. However, based on previous findings concerning weight recall for Brazilian women studied outside of pregnancy 10 and other studies about referred weight, 2 it seems that weight measure bias is probably small. As a conclusion, overweight nutritional status is highly prevalent among women seen in prenatal public clinics of major Brazilian cities, even for the age range of 20-24 years.…”
Section: Discussionmentioning
confidence: 92%